Impact of Comorbidities on Acute Injury and Recovery in Preclinical Stroke Research: Focus on Hypertension and Diabetes - Ergul, Adviye (Transl Stroke Res, 2016)
Human ischemic stroke is very complex and no single preclinical model can comprise all the variables known to contribute to stroke injury and recovery. Hypertension, diabetes and hyperlipidemia are leading comorbidities in stroke patients. The use of predominantly young adult and healthy animals in experimental stroke research has created a barrier for translation of findings to patients. As such, more and more disease models are being incorporated into the research design. This review highlights the major strengths and weaknesses of the most commonly used animal models of these conditions in preclinical stroke research. The goal is to provide guidance in choosing, reporting and executing appropriate disease models that will be subjected to different models of stroke injury.